Do Employer Preferences Contribute to Sticky Floors? - Stijn Baert; Ann-Sophie De Pauw; Nick Deschacht (Institute for the Study of Labor (IZA), 2014)
We investigate the importance of employer preferences in explaining Sticky Floors, the pattern that women are, compared to men, less likely to start to climb the job ladder. To this end we perform a randomised field experiment in the Belgian labour market and test whether hiring discrimination based on gender is heterogeneous by the promotion characteristics of the selected jobs. We find that women get 33% less interview invitations when they apply for jobs implying a first promotion in functional level. On the other hand, their hiring chances are not significantly affected by the job authority level of the job.
Keywords: J16; J71; M51; J41; C93; 330; sticky floors; gender discrimination; hiring discrimination; labour market transitions; European labour markets